FORMATION OF LOGICAL CULTURE OF SENIOR STUDENTS IN THE STUDY OF INFORMATICS (Pedagogy of Higher and Secondary Education, 2004)
In this article opened the system of educational exercises on development of logic culture of senior pupils at lessons of computer science.